Comedonal graft‐vs‐host disease: a distinct clinical expression of a lichenoid follicular GVHD. (28th October 2014) - Llamas‐Velasco, Mar; Solano‐López Morel, Guillermo Enrique; Gruber‐Wackernagel, Alexandra; Concha‐Garzón, Maria Jose; Requena, Luis; Cerroni, Lorenzo
<x xml:space="preserve">Abstract</x> We report two cases of chronic follicular graft‐vs‐host disease (GVHD) that resemble closed and open acne‐like comedones. We propose the term 'comedonal GVHD' for this variant. A 47‐year‐old man presented with multiple 2–4‐mm acne‐like follicular papules in facial areas on day 82 status post bone marrow transplantation. A biopsy showed follicular infundibular dilation with keratotic plugs, hypergranulosis and vacuolar alteration (hydropic degeneration) of the basal layer, with dyskeratotic (apoptotic) keratinocytes, scattered lymphocytes and vascular ectasia of the superficial dermal plexus. We diagnosed chronic follicular lichenoid GVHD. The second patient was a 53‐year‐old female. On day 420 after transplantation, she presented with generalized dark to grayish, confluent, indurated lesions with confluent papules and unevenly distributed comedo‐like lesions. Skin biopsy showed sclerotic dermis and also dilated follicular infundibula with keratotic plugging, hypergranulosis and vacuolar alteration (hydropic degeneration) of the basal layer of the epidermis. We established the diagnosis of chronic sclerodermoid GVHD with follicular lichenoid involvement. The presence of open and closed comedones on the trunk and facial region of an adult raises several differential diagnosis but in our patients, histopathologic study demonstrated typical features of GVHD, which led to this diagnoses despite the peculiar clinical findings.